2017
DOI: 10.1021/jacs.7b09025
|View full text |Cite
|
Sign up to set email alerts
|

A N-Heterocyclic Carbene-Stabilized Coinage Metal-Chalcogenide Framework with Tunable Optical Properties

Abstract: A new class of coinage-metal chalcogenide compounds [AuM(μ-E)(IPr)] (M = Ag, Au; E = S, Se, Te) has been synthesized from the combination of N-heterocyclic carbene-ligated gold(I) trimethylsilylchalcogenolates [(IPr)AuESiMe] and ligand-supported metal acetates. Phosphorescence is observed from these clusters in glassy 2-methyltetrahydrofuran and in the solid state at 77 K, with emission energies that depend on the selection of metal/chalcogen ion composition. The ability to tune the emission is attributed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 57 publications
3
41
0
Order By: Relevance
“…343 Recent reports of gold clusters with NHC ligands include the Au 8 cluster bearing bridging sulfide ligands described by Corrigan and co-workers, in which a central Au 4 core is supported by bridging sulfide ligands, and surrounded by four additional Au atoms each bound to an N-heterocyclic carbene (Scheme 71). 344 Shionoya and co-workers described a dicationic carboncentered hexagold(I) cluster stabilized by N-heterocyclic carbene ligands (Scheme 72), 345 similar to those reported by Schmidbaur with phosphine ligands, which also showed luminescent properties.…”
Section: Gold Clusterssupporting
confidence: 54%
“…343 Recent reports of gold clusters with NHC ligands include the Au 8 cluster bearing bridging sulfide ligands described by Corrigan and co-workers, in which a central Au 4 core is supported by bridging sulfide ligands, and surrounded by four additional Au atoms each bound to an N-heterocyclic carbene (Scheme 71). 344 Shionoya and co-workers described a dicationic carboncentered hexagold(I) cluster stabilized by N-heterocyclic carbene ligands (Scheme 72), 345 similar to those reported by Schmidbaur with phosphine ligands, which also showed luminescent properties.…”
Section: Gold Clusterssupporting
confidence: 54%
“…Atom‐precise metal chalcogenolate nanoclusters are a new category of materials with many unusual properties, the most important of which is luminescence . Among them, low‐cost Ag chalcogenolate clusters (SCCs) remain largely unexplored in contrast to Au thiolate clusters, and currently their structure–luminescence correlations are poorly understood. Structural isomers and pseudoisomers are excellent species to investigate structure–property relationships, which are favorable for guiding the design and synthesis of unique functional materials.…”
Section: Figurementioning
confidence: 99%
“…[37][38] Several coinage metal clusters stabilized by NHCs have been prepared as well. [39][40][41] Theoretical work also suggested that NHCs may function as new ligands for gold surface modification and NCs protection. 42 Given these reports, it occurs to us that NHCs may mimic tertiary phosphines as a new class of ligands in stabilizing metal clusters, and may be a game-changer in metal cluster chemistry.…”
Section: Introductionmentioning
confidence: 99%